Public Library Computer Waiting Queues: Alternatives to the First-Come-First-Served Strategy - Stuart Williamson (Information Technology and Libraries, 2012)
This paper summarizes the results of a simulation of alternative queuing strategies for a public library computer sign-up system.  Using computer usage data gathered from a public library, the performance of these various queuing strategies is compared in terms of the distribution of user wait times.  The consequences of partitioning a pool of public computers are illustrated as are the potential benefits of prioritizing users in the waiting queue according to the amount of computer time they desire.